Population Pharmacokinetic Analysis of Dalteparin in Pediatric Patients With Venous Thromboembolism. (21st August 2020) - Damle, Bharat; Jen, Frank; Sherman, Nancy; Jani, Darshana; Sweeney, Kevin
Abstract: This article describes the population pharmacokinetics (PK) of dalteparin in pediatric patients with venous thromboembolism (VTE). A prospective multicenter open‐label study was conducted in children who required anticoagulation for the treatment of VTE. The study population included children with and without cancer. The goal was to describe the pharmacokinetics of dalteparin using anti‐Xa as a surrogate marker and to determine the dose required to achieve therapeutic anti‐Xa levels (0.5‐1.0 IU/mL). The anti‐Xa data were supplemented with 2 published studies and analyzed using population pharmacokinetic approaches. The pharmacokinetics of dalteparin following subcutaneous injection in pediatric patients was described by a 1‐compartment model with linear absorption and elimination. Body weight was added as a covariate on both CL/F and Vd/F as a power function with fixed exponents of 0.75 and 1.0, respectively. The estimates of CL/F and Vd/F in the full model were 929 mL/h and 7180 mL, respectively, for a reference female patient aged 12 years with body weight of 43 kg. Body weight‐normalized CL/F decreased with age. Cancer status and sex did not have significant effects on CL/F and Vd/F. Simulations were conducted to select starting doses of dalteparin that would rapidly achieve therapeutic anti‐Xa levels. These simulations suggested that the recommended starting doses of dalteparin administered subcutaneously in pediatric patients of different age cohort groups for treatment of VTE were 150 IU/kg every 12 hours (1 month to <2 years), 125 IU/kg every 12 hours (≥2 to <8 years), and 100 IU/kg every 12 hours (≥8 to <19 years).